2022
DOI: 10.1039/d2gc03082a
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-assembled gel monolithic microreactor for continuous flow asymmetric synthesis of aryl alcohols

Abstract: The green, efficient, and sustainable flow synthesis of intermediate chiral aryl alcohols is critical for continuous drug-manufacturing. Enzyme immobilization endows flow biocatalysis with higher application potential, however, conventional methods are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Chiral alcohols are valuable building blocks used in the synthesis of, particularly, pharmaceuticals, agrochemicals, and fine chemicals and have drawn extensive attention in the field of catalysis. A considerable number of significant active intermediates and top-selling drugs contain chiral alcohol moieties. In the context, ( S )-1-phenylethanol can be employed as a synthetic precursor to prepare sertraline for treating depression, asmalar for treating asthma, and levamisole for enhancing the immune system. ( R )-2-chloro-1-phenylethanol and ( S )-1-(2,6-dichloro-3-fluorophenyl)-ethanol are the intermediates for synthesizing fluoxetine and crizotinib, respectively. , (+)-Bacillamide exhibits anti-HIV activities and lovastatin displays potential for the prevention and treatment of various types of cancers and cholesterolemic and neurological disorders (Figure ). , The classical synthetic procedures of chiral alcohol compounds usually rely on harsh reaction conditions such as high pressure and temperature, expensive chiral ligands, and environmentally unfriendly organic reagents. Therefore, developing efficient, economical, and sustainable routes for chiral alcohol synthesis is urgently needed owing to the rising shortage of resources and environmental concerns. , Various oxidoreductases such as ketoreductases (KREDs), also known as alcohol dehydrogenases (ADHs), have been employed for the asymmetric reduction of ketones to produce chiral alcohols for their merits of excellent enantioselectivity, specificity, and benign conditions. , However, more than 80% of enzymatic reductions from ketones catalyzed by oxidoreductases require a cofactor NAD­(P)H as the hydrogen source to be consumed for accomplishing catalytic functions. , In the last decades, extensive efforts have been made toward exploring simple and suitable methods for cofactor regeneration. ,, Despite the significant progress that has been made in the regeneration of NAD­(P)H via biocatalytic, electrochemical, and photochemical methods, biocatalysts that do not rely on cofactors for the fabrication of chiral alcohols still remain to be further explored. , Recently, a human carbonic anhydrase II (hCAII) was reported that exhibited excellent catalytic activity and enantioselectivity in the asymmetric reduction of ketones with silanes as the reductant .…”
Section: Introductionmentioning
confidence: 99%
“…Chiral alcohols are valuable building blocks used in the synthesis of, particularly, pharmaceuticals, agrochemicals, and fine chemicals and have drawn extensive attention in the field of catalysis. A considerable number of significant active intermediates and top-selling drugs contain chiral alcohol moieties. In the context, ( S )-1-phenylethanol can be employed as a synthetic precursor to prepare sertraline for treating depression, asmalar for treating asthma, and levamisole for enhancing the immune system. ( R )-2-chloro-1-phenylethanol and ( S )-1-(2,6-dichloro-3-fluorophenyl)-ethanol are the intermediates for synthesizing fluoxetine and crizotinib, respectively. , (+)-Bacillamide exhibits anti-HIV activities and lovastatin displays potential for the prevention and treatment of various types of cancers and cholesterolemic and neurological disorders (Figure ). , The classical synthetic procedures of chiral alcohol compounds usually rely on harsh reaction conditions such as high pressure and temperature, expensive chiral ligands, and environmentally unfriendly organic reagents. Therefore, developing efficient, economical, and sustainable routes for chiral alcohol synthesis is urgently needed owing to the rising shortage of resources and environmental concerns. , Various oxidoreductases such as ketoreductases (KREDs), also known as alcohol dehydrogenases (ADHs), have been employed for the asymmetric reduction of ketones to produce chiral alcohols for their merits of excellent enantioselectivity, specificity, and benign conditions. , However, more than 80% of enzymatic reductions from ketones catalyzed by oxidoreductases require a cofactor NAD­(P)H as the hydrogen source to be consumed for accomplishing catalytic functions. , In the last decades, extensive efforts have been made toward exploring simple and suitable methods for cofactor regeneration. ,, Despite the significant progress that has been made in the regeneration of NAD­(P)H via biocatalytic, electrochemical, and photochemical methods, biocatalysts that do not rely on cofactors for the fabrication of chiral alcohols still remain to be further explored. , Recently, a human carbonic anhydrase II (hCAII) was reported that exhibited excellent catalytic activity and enantioselectivity in the asymmetric reduction of ketones with silanes as the reductant .…”
Section: Introductionmentioning
confidence: 99%
“…Chiral aryl alcohols as valuable intermediates used in the synthesis of fine chemicals and particularly pharmaceutical drugs have received extensive attention. 1,2 Presently, developing economical, efficient, and sustainable synthetic processes for value-added chemical manufacturing has become an urgent requirement due to worldwide environmental concerns and rising shortage of resources. 3,4 Asymmetric reduction of prochiral ketones catalyzed by oxidoreductases such as ketoreductases (KREDs) or alcohol dehydrogenases (ADHs) has emerged as an appealing approach for producing chiral alcohols due to the merits of excellent enantioselectivity, benign condition, and efficient synthetic routes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chiral aryl alcohols as valuable intermediates used in the synthesis of fine chemicals and particularly pharmaceutical drugs have received extensive attention. , Presently, developing economical, efficient, and sustainable synthetic processes for value-added chemical manufacturing has become an urgent requirement due to worldwide environmental concerns and rising shortage of resources. , Asymmetric reduction of prochiral ketones catalyzed by oxidoreductases such as ketoreductases (KREDs) or alcohol dehydrogenases (ADHs) has emerged as an appealing approach for producing chiral alcohols due to the merits of excellent enantioselectivity, benign condition, and efficient synthetic routes. However, over 80% of the oxidoreductase nature depends on the cofactor NAD­(P)H to accomplish catalytic functions, limiting further applications of many enzyme catalytic processes due to the expensive and unstable properties of the cofactor. , Thus, different strategies including enzymatic, chemical, electrochemical, and photocatalytic reduction have been developed to regenerate the cofactor in situ . …”
Section: Introductionmentioning
confidence: 99%